A closer look at formation control - Qian, Dianwei (Computer science, technology and applications., 2020)
"Formation control is one of the most challenging problems in cooperative multi-robots. It is defined as a coordination of a group of robots to get into and to maintain a formation with a certain shape. The formation control problem has drawn significant attention for many years, and now it is well understood and tends to be mature. This control problem is originated from biological inspires such as flocking and schooling. Its classification includes formation shape generation, formation reconfiguration and selection, formation tracking, and role assignment in formation. It also has potential applications in search and rescue missions, forest fire detection and surveillance, etc. It can be extended to many real world systems, autonomous robots, such as underwater vehicles, unmanned aerial vehicles, mobile sensor networks, rectangular agents, nonholonomic mobile robots, to name but a few. Apparently, the book cannot include all research topics. The editor and the authors wish that it could reveal some tendencies on this research field and benefit readers. In this book, different aspects of formation control are explored. Chapters includes some new tendencies and developments in research on several formation methods of multi-robot systems, that is, the 1st-order sliding mode control, the 2nd-order sliding mode control, the integral sliding mode control, the terminal sliding mode control, the sliding model control of multi-agents and the fuzzy-based formation control of multiple quadrotor systems"--